EVALUASI SISTEM DAN PROSES PENGAJARAN TERHADAP LULUSAN AKPOL 2006 – 2010 DI WILAYAH POLDA NUSA TENGGARA BARAT (NTB) - Cecep Tedi Siswanto; Puguh Windrawan (Kajian Hukum, 2017)
This assessment is linked to the respondent answers given to the questions given. The question that is open and qualitatively reflect the depth of their thoughts on the situation at hand. Along with the fact that there are some things that concern in it. This is related to internal accountability that is in the body of the local police.      Like what is described by M. Adiel Ipda Aristo, Kanit Regident Then Bima City and Ipda Cita gift Sari, Chief of Unit 2 Satreskrim Idik West Lombok Police. Internal issues such as the perception of his colleagues to the position Ipda M. Adiel Aristo, which considers that the position is a "wetland". While Ipda Cita gift of Sari complained about the police in his unit were involved indirectly with drugs.      Internal accountability become one of the requirements that the police force be an institution which kredibel. Bagaimanapun also for police officers with paradigm still had not moved from the old and still engage in certain cases, the negative connotations and stigma is still attached to the institution in the public eye.In accordance with the concepts of accountability, then the top level should be able to resolve cases related to subordinates. Moreover, decisive action and their internal control, both the police personnel, to operations conducted and to the reporting of performance, accompanied by a system of sanctions and rewards, an absolute requirement that must be done.Being a thing that can not go unnoticed is the inconsistency of the respondents to the concept of human rights. They stated that the concept of human rights is actually needed in bridging the behavior of the police when dealing with the public. However, this attitude changed when the concept of human rights is then translated in the field. Some respondents considered the concept of human rights will collide with reality. It became one of the proofs that the objective and purpose of the issuance of Police Regulation No. 8 Year 2009 on Implementation Principles and Standards of Human Rights in the Implementation Task Indonesian National Police, has not been applied to the maximum on the idea 2006- 2010 graduate of the Police Academy.